Retracted: Application and Development of Big Data in Sustainable Utilization of Soil and Land Resources - Zhaoya Chen; Wei Huang; Lijun Ma; Hao Xu; Yaheng Chen (IEEE Access)
Land is an important part of our living environment. As far as China is concerned, the research on Sustainable Utilization of land resources is relatively late. At present, there is not a complete set of principles of land resource evaluation index system in China. The relevant research is more theoretical, and the actual application cases are less. In the context of the urgent need for development of the national economy, it is an urgent problem to improve the sustainable utilization rate of land resources, which will directly affect the structural reform and the overall strategy of our country. Therefore, based on the big data of the Internet of things, combined with RS and GIS and other related intelligent technologies, this paper establishes a set of evaluation model for the sustainable use of land resources. The method in this paper is to establish the index evaluation system first, then carry out data preprocessing through GIS and RS technology, and finally use big data technology for data mining. According to the actual situation of land resources in China, Delphi method is used as the main qualitative technical analysis method to set a reasonable weight for the evaluation index system of land resources. In order to verify the effect of this method, when analyzing the land resource data of a county from 2009 to 2018, this paper carried out four experiments including the overall trend analysis of land sustainable utilization. The experimental data results show that the use of big data in this paper has achieved ideal results in the application of land resource sustainable utilization, and to a certain extent, it fills in the big data and land The case study in the field of sustainable utilization of resources is a good method and has a broad application prospect.